An investigation into the English language experiences of Indian international students studying in New Zealand universities. Issue 3 (15th April 2020) - Kukatlapalli, Johnson; Doyle, Stephanie; Bandyopadhyay, Sekhar
ABSTRACT: Language proficiency is highlighted in the literature on the adjustment and security of international students. India is the second top source country for mobile students globally, but few studies have focused explicitly on students from India. The purpose of this study was to examine the English language experiences of Indian students at New Zealand universities. This mixed-method study utilised a questionnaire ( n = 109) and interviews ( n = 15). Collectively the participants had high levels of confidence and proficiency in English language and adjusted more rapidly than many international students to the new academic environment. Major differences experienced by the participants between India and New Zealand related to unfamiliar forms of academic writing and tasks, and on the role of learning support services. Formal high value assessment was for some the first indication of a problem with writing. While most students adjusted through error-based learning others struggled with argumentation and avoiding plagiarism. These findings have relevance for local and international students. We recommend the use of, and research on, early low-stakes assessment of writing and on effective support services for students transitioning into new academic contexts.